Modeling of temperature fields in the working chamber of the process furnace for REE synthesis; IOP Conference Series: Materials Science and Engineering; Vol. 110 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2015) - Kerbel B. M.; Ageev A. Yu.; Payusov A. Yu.; Katsnelson L. M.; Tereshchenko E. V.; Verkhoturova V. V. Vera Viktorovna (2016, 2016)
Title screen